B. F. Skinner’s Verbal Behavior: a retrospective appreciation. (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Artigo clássico traduzido do inglês, publicado originalmente no periódico Journal of the Experimental Analysis of Behavior sem resumo.